Synthesis and Characterization of Some Bis-Nitroaryl Pyrazolonesand Estimation of Their Anti-Bacterial and Anti-Fungal Activities - MuathJabbarTarfa Al-Abbasee1, Hamid J. Mohammad2, Mawlood K. Mawlood1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A simple and efficient one-pot synthesis of bicyclic nitro pyrazolone derivatives in traditional alcoholic solvents under refluxing conditions, The chemical structure of the synthesized derivatives was substantiated byFT-IR,1H NMR ,13C-NMRand CHNS analysis, All of these compounds of the series have been testedin vitro asantibacterial and antifungalagents against four types of organisms. The minimum and maximum inhibitory concentrations were determined against each organism.